Morfometrik dan Meristik Ikan Cupang(Trichopsis Vittata) di Waduk Fakultas Perikanan dan Kelautan Universitas Riau dan Parit Besar Perumdam - Tanjung, Nevy Arizky; Windarti, Windarti; Efizon, Deni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Trichopsisvittata is one of the freshwater fish that commonly present in Riau, including in the Riau University Dam and the main ditch of the PERUMDAM housing complex. Information on the biological aspects of these fish, including the morphometric, meristic and growth patterns, however, is rare. To understand the morphometric and characteristics of these fish, a study was conducted from October-December 2019. The fish was sampled from 2 locations, namely in the Riau University Dam and in the main ditch of the PERUMDAM housing complex, 4 times, once/ week. There were 200 fishes captured, 100 fishes from the dam and 100 fishes from the ditch. They were 29-54 mm SL and 4.12-5.7 g BW. Twenty six morphological characteristics measured and 11 meristic characteristics were studied. Results shown that the meristic characteristics are as follows D.II.6-8, P.6-8, V.5-10, A.VI-VII.24-28, C.11-13.The number of scales in the dorsal fin was 12-18 in the cheek was 8-9, around the body was 38-40, in the tail basewas 14-16, above the lateral line was 6-8 and below the lateral line was 10-12. There were 3 differences of morphometric characteristics between male and female of Trichopsisvittata. In male, the distances betweenmouthand the base of the pectoral fin, the abdominal fin to the base of the anal fin and the length of the anal fin is longer than those of the female’s. The length-weight relationship of female (b = 0.222) and the male (b = 0.302) was negative allometric. Keywords:freshwater fish, negative allometric, growth patterns, fish morphology